Review Of Law And Human Rights Regarding The Granting Of Dispensation In Minor Marriage - Liatunisa, Hilda; Daming, Saharuddin; Ratnawaty, Latifah (JURNAL MAHASISWA YUSTISI, 2025)
Marriage is a way for individuals to bind themselves to another person in a sacred bond. Essentially, adults marry because they are considered mentally mature and ready, both physically and emotionally. Article 7, paragraph (1) of Law Number 16 of 2019, which amends Law Number 1 of 1974, stipulates that men and women may marry when they reach the age of 19. According to paragraph (2), if they marry before reaching this age, the parents of the husband or wife can request an exception from the court. Essentially, the regulations in Indonesia do not specify the reasons or characteristics of children who are granted the freedom to marry, so it is the judge who decides whether the child is entitled to such freedom. The purpose of this research is to examine the factors and reasons for someone to apply for a marriage dispensation for underage children, the legal consequences if the child is granted the dispensation, and to understand the considerations of the judge in granting the marriage dispensation for underage children. The research used in this thesis is normative juridical research, which is conducted by studying laws, legal doctrines, and legal principles. This research can be conducted using a document analysis method, which is a normative juridical research method carried out by reviewing laws, legal doctrines, and legal principles. This research can be conducted through a document analysis method, which is a normative jurisprudence research method that involves examining laws, jurisprudence, and legal principles. However, the reasoning remains consistent, and the judge's opinion is neutral and consistent, which is to release while drawing benefits and not causing harm. In the category of adults, the judge also relies on Islamic law, which uses a person's intellect and puberty to be counted as an adult. It is hoped that the government will issue regulations that outline the characteristics or basis for someone to apply for a court exemption.